(untitled) (Veterinary Science, 2026)
Canine mammary adenocarcinomas are the most common neoplasm, accounting for 50% of malignant cases. Although surgical excision is the main treatment and adjuvant chemotherapy improves survival, the prognosis is usually poor, with high metastasis to lymph nodes and lungs. This study correlates findings obtained through imaging techniques with histopathological analysis in a clinical case of a 10-year-old female Siberian Husky. Radiographs ruled out distant metastasis. Breast ultrasound revealed heterogeneous masses with irregular and poorly defined edges, hypoechoic and hyperechoic areas, increased vascularization, microcalcifications, and anechoic areas due to necrosis. This ultrasound pattern was highly suggestive of malignancy, which coincided with histopathological analysis confirming the presence of a complex carcinoma, a malignant epithelial neoplasm characterized by two cell populations. The ultrasound characteristics correlated directly with the histology, with the hypoechoic areas corresponding to the malignant epithelial component and necrosis, and the hyperechoic areas corresponding to the benign fibrous stroma. This allows us to conclude that ultrasound, an accessible routine tool, can provide a highly reliable presumptive diagnosis of malignant mammary adenocarcinoma. The described pattern would justify the recommendation of total surgical removal, with histological biopsy reserved for definitive confirmation and determination of tumor grade, which is crucial for prognosis and subsequent treatment. This correlation improves diagnosis and contributes to comparative oncology, which supports the use of canine models for the study of breast cancer